Sand Dune Stabilization in the Thar Desert of India: A Synthesis - Kaul, R N (Annals of Arid Zone, 2016)
Sand dune stabilization programme in the Thar desert of India is based on an understanding of the edaphic characteristics of the dune-interdune systems, as well as on the soil-water-plant relationships of the major dune types. A number of physical and chemical methods of stabilization have been tried during the last four decades. It has been found that the more lasting effects are achieved through a careful plantation of trees, shrubs and grasses at appropriate sites and using proven technologies. There is, however, a need to further refine the techniques to suit the different dune environments and to make the venture economically more viable.